Benchmarking: methods and tools for SME - Maire, Jean-Luc; Bronet, Vincent; Pillet, Maurice (Benchmarking : an international journal, 2008)
Purpose - The purpose of this paper is to present a benchmarking process that can assist small to medium-sized enterprises (SME).Design methodology approach - The paper describes how the steps of a benchmarking process can be positioned with the steps of the plan-research-observe-analyzes-adapt-improve cycle (PROAAI) and shows that the tools proposed to carry out these steps are mostly reserved for big companies. We therefore detail a set of tools and methods to assist SMEs in the deployment of the steps of a benchmarking process (observe and analyse steps).Findings - The tools and methods which are described in this paper especially target the description of the processes (process to be improved and reference process) using the description of the current practices used, and the comparison of these processes leading to suggestions of improvements to carry out on the process to improve.Research limitations implications - In this paper, the identification of the subject to be benchmarked is currently based on a description of the differences observed between a reference process and the process to be improved. Our future research is to determine how just one interview could be carried out instead of two.Practical implications - The methods and tools have been applied in several manufacturing plants at TECUMSEH Europe.Originality value - Practical help to a SME to carry out a benchmarking.